Up in Smoke: Biomass Burning, Land Cover Change, and Atmospheric Emissions in the Sudanian Savannas of Côte d’Ivoire - Koné, M.; Bassett, T.J.; Nkem, J. (Norman E. Borlaug Leadership Enhancement in Agriculture Program, 2008)
The environmental change literature depicts West African savanna fires as intense and highly destructive. It assumes that burning takes place in the middle and late-dry seasons, views African savannas as one of the “burn centers” of the planet, and considers biomass burning to be an important source of greenhouse gas emissions. The research presented in this brief, however, took a political-ecological approach to advance the understanding of burning regimes and to present a more accurate assessment of land use and land cover change in the Sudanian savannas of Côte d’Ivoire. Findings show that contemporary agricultural and pastoral practices generate early fires that result in low burning intensity, more frequent and small fires, and inefficient combustion. The results also show that the Sudanian savannas are complex and differentiated ecosystems composed of several vegetation types, and that grass biomass load is declining while woody vegetation cover is increasing over time. Increased tree vegetation cover will sequester more carbon dioxide. The knowledge generated here is crucial for environmental decision-making. Updated and accurate environmental information is critical for formulating sound environmental policies. The findings are particularly relevant to current debates on the environmental impact of agricultural and pastoral systems in West Africa and to policy discussions focused on global climate change.